Estimated Value of Procurement in the Context of Awarding Public Contracts and Control Over Them - Goranova, Ilonka (Research Papers, 2021)
The aim of the following paper is to draw attention to the importance of the estimated value of public procurement and to discuss some related legal issues. This will be achieved through practice-oriented analysis of current legislation from administrative law standpoint. The main task of the research is to derive, systematize and analyze the relevant provisions of Bulgarian and, where necessary, European legislation. Compliance with these provisions is of utmost importance, to ensure that public funds are spend in line with the law. Applicable rules for awarding, as well as whether a specific public procurement shall be subject to external preliminary control by the Public Procurement Agency or not, are determined based on the estimated value. Failure to comply with mandatory provisions would lead to the imposition of fines on the contracting authority and the contracting entity, financial corrections, as well as ineffectiveness of contracts and framework agreements. The study could assist: (i) contracting authorities and contracting entities in the correct planning, as well as awarding of public contracts lawfully; (ii)control bodies – in the exercise of their powers; (iii) economic operators – in connection with their participation in public procurement procedures.
Keywords: Public procurement; Estimated value of procurement; Subsidised contracts; Separate lots; Mixed procurement; Maximum yearly turnover requirement; External preliminary control